Animal stories for seven year olds - "Paiba , Helen" "Paiba, Helen" (Macmillan Childrens Book: London, 1998)
Fifteen animal stories are featured in this book, including those on kittens and kangaroos, and puppies and ponies. There are stories from the past and present, and from around the world
Keywords: Animals fiction